Development of bacteriophage ΦKAZ14 loaded chitosan nanoparticles for biological control of colibacillosis in chickens - Kaikabo, Adamu Ahmad (2016)
Bacteriophage ΦKAZ14 was applied in the biological control of colibacillosis. It had lytic activity on APEC 01: K1:H7 and β lactamase producing Escherichia coli. The icosahedral head of the phage measured 50 nm by 45 nm and long contractile tail of 78 nm by 10 nm. It multiplicity of infection (MOI) was 0.01, the latent period of infection of 15 minutes and burst size of 80 particles per infected cell. The phage survived a pH range of 5.0 to 14, and resistant to a temperature of 65 °C. C-NPs protected the phage from enzymatic degradation in vitro. The spherical C-NPs had average particle size range from 176 ± 3.2 to 188 ± 7.4 nm, a zeta potential of 60.3±0.2 and 50.5±0.4 and polydispersity index (PDI) of 0.506 and 0.472. Fourier transform infrared spectroscopy (FTIR) showed no difference between C-ΦKAZ14 NP and C-NP. Thermal analysis showed the temperature of -20 °C is desirable for storage. C-ΦKAZ14 NPs were not toxic on chorioallantoic membrane. Treatment with C- ΦKAZ14 NPs decrease viable bacterial counts in feces and colonization in the intestine of chickens (p ≤ 0.05). It also significantly decreased mortality rate in E. coli-challenged birds (p ≤ 0.05). C- ΦKAZ14 NPs increased bodyweight of chickens (p ≤ 0.05). Lesions were not observed in major organs. C- ΦKAZ14 NPs therapy is a beneficial control strategy against colibacillosis in chickens.